Family Quality of Life and Partnership for Families of Students With Deaf-Blindness. (February 2020) - Kyzar, Kathleen; Brady, Sara; Summers, Jean Ann; Turnbull, Ann
Family–professional partnerships are a key support for families of children with disabilities, but little is known about families of children with deaf-blindness. This study examined (a) the factor structures of the Beach Center on Disability Family–Professional Partnership and Family Quality of Life (FQOL) Scales utilizing a national sample of families of children and youth with deaf-blindness (age birth to 22 years), and (b) the relationship between family–professional partnership and FQOL at the subdomain levels. Results suggested a two-factor solution for family–professional partnership (Enhancing Connection and Enhancing Capacity) and a three-factor solution for FQOL (Family Interaction/Parenting Well-being, Social/Emotional Well-being, Physical/Material Well-being). Enhancing Capacity Partnership moderated the relationship between Enhancing Connection Partnership and Family Interaction/Parenting Well-being FQOL. The significance of these findings in light of the existing family–professional partnership literature is discussed, and implications for research and practice are offered.